2019
DOI: 10.3390/app9050987
|View full text |Cite
|
Sign up to set email alerts
|

Spam Review Detection Techniques: A Systematic Literature Review

Abstract: Online reviews about the purchase of products or services provided have become the main source of users’ opinions. In order to gain profit or fame, usually spam reviews are written to promote or demote a few target products or services. This practice is known as review spamming. In the past few years, a variety of methods have been suggested in order to solve the issue of spam reviews. In this study, the researchers carry out a comprehensive review of existing studies on spam review detection using the Systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 67 publications
(77 reference statements)
0
28
0
Order By: Relevance
“…Systematic literature review (SLR) provides answers to certain research questions [11]. The stages in a systematic literature review are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Systematic literature review (SLR) provides answers to certain research questions [11]. The stages in a systematic literature review are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…This section elaborates the proposed spammer behavioral method and analyzes the performance of the method in terms of accurate identification of spam reviews. Since a spammer can be identified by analyzing its different behavioral features, therefore, unlabelled dataset can be used with unsupervised learning to identify the spam reviews [31], [32]. The proposed Spammer Behavioral Method (SRD-BM) takes unlabelled dataset and produces an output of a labelled dataset that identifies spam and not spam reviews.…”
Section: Spam Review Detection Using the Spammer Behavioral Methomentioning
confidence: 99%
“…Each node is divided into sub-categories by defining the level of categorization. Hussain et al [10] detail the spam review detection techniques in 2-4 level tree depth. Meanwhile, Gupta et al [11] present multiple taxonomies related to phishing attacks.…”
Section: Visualization Forms Of Phishing Attack Taxonomiesmentioning
confidence: 99%